2011
DOI: 10.1038/eye.2011.319
|View full text |Cite
|
Sign up to set email alerts
|

Silicone oil removal after rhegmatogenous retinal detachment: comparing techniques

Abstract: Purpose To assess the outcome of silicone oil removal after rhegmatogenous retinal detachment (RRD) surgery, and to compare results of a two-port (infusion-extraction) versus a three-port (full vitrectomy) approach. Methods Primary outcome measure was the rate of redetachment. Secondary outcome measures were visual acuity, rate of intraoperative and postoperative epiretinal membrane removal and complications. Results We included 147 consecutive cases. There were 15 cases of giant retinal tear, 26 cases of RRD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
2
14
0
Order By: Relevance
“…In this study, the relation between duration of silicone oil tamponade and incidence of retinal redetachment was not established. In the literature, while some authors did not consider the timing of silicone oil removal as a risk factor for anatomic success rate [4,8,9], others observed that shorter tamponade duration had lower attachment rate than longer tamponade duration [10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the relation between duration of silicone oil tamponade and incidence of retinal redetachment was not established. In the literature, while some authors did not consider the timing of silicone oil removal as a risk factor for anatomic success rate [4,8,9], others observed that shorter tamponade duration had lower attachment rate than longer tamponade duration [10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…More often than not, the patients with fungal endophthalmitis may have only minor discomfort. [2][3][4] Similarly, not all clinicians agree with the routine use of intravitreal antibiotics in prophylaxis. 5 In patients with open globe injuries and traumatic endophthalmitis, there is always a risk of associated retinal detachment or choroidal detachment.…”
Section: Sir Post-traumatic Endophthalmitismentioning
confidence: 99%
“…Before instituting antifungal treatment, distinguishing fungal from bacterial post-traumatic endophthalmitis is important because the treatments are different and prophylactic antifungal treatment can be toxic both systemically or locally. [2][3][4] A clinical feature that suggests fungal infection is a delayed onset of inflammation after injury. [2][3][4] Literature search has reported that all post-traumatic cases of fungal endophthalmitis became symptomatic between the first and fifth weeks after injury, with minimal discomfort to the patient.…”
Section: Sir Post-traumatic Endophthalmitismentioning
confidence: 99%
See 2 more Smart Citations